ANALISA KADAR FOSFAT DAN NITRIT PADA SAMPEL AIR DANAU DENGAN MENGGUNAKAN METODE SPEKTROFOTOMETRI - Marlisa Roro Putri; Bohari Yusuf; Ika Yekti Lianasari (PROSIDING SEMINAR KIMIA, 2025)
Lake water plays an important role as a water resource and as a habitat for aquatic ecosystems. However, increasing human activities around the lake have led to pollution, particularly by phosphate and nitrite compounds originating from domestic and industrial waste. This study aims to determine the levels of phosphate and nitrite in lake water samples from the southern (AP1) and western (AP2) parts of the Polder using the UV-Vis spectrophotometry method. Phosphate analysis was conducted based on SNI 6989.31:2005, and nitrite analysis was based on SNI 06-6989.9-2004 using a UV-Vis spectrophotometer. The results showed that phosphate levels in samples AP1 and AP2 were 0.053 mg/L and 0.046 mg/L, respectively, while nitrite levels at both points were 0.055 mg/L. These parameters are still below the quality standard thresholds set by Government Regulation No. 22 of 2021. These findings indicate that the water quality of the Polder lake still meets the established environmental standards. Therefore, the UV-Vis spectrophotometry method is effective for water quality monitoring, and the results of this study can serve as a basis for sustainable aquatic environmental conservation efforts. Keywords: Lake, Phosphate, Nitrite and UV-Vis Spectrophotometer.